A new multi-criteria optimization strategy for shared control in wheelchair assisted navigation - Urdiales-García, Amalia Cristina; Peula Palacios, José Manuel; Fernández-Carmona, Manuel; Barrue, Cristian; Perez, Eduardo Jesús; Sanchez-Tato, Isabel; del Toro, Jose Carlos; Galluppi, F.; Cortés, Ulises; Annichiaricco, Roberta; Caltagirone, Carlo; Sandoval-Hernández, Francisco (Springer, 2010)
In todays aging society, many people require mobility assistance, that can be provided by robotized assistive wheelchairs with a certain degree of autonomy when manual control is unfeasible due to disability. Robot wheelchairs, though, are not supposed to be completely in control because lack of human intervention may lead to loss of residual capabilities and frustration. Most of these systems rely on shared control, which typically consists of swapping control from human to robot when needed. However, this means that persons never deal with situations they find difficult. We propose a new shared control approach to allow constant cooperation between humans and robots, so that assistance may be adapted to the user’s skills. Our proposal is based on the reactive navigation paradigm, where robot and human commands become different goals in a Potential Field. Our main novelty is that human and robot attractors are weighted by their respective local efficiencies at each time instant. This produces an emergent behavior that combines both inputs in an efficient, safe and smooth way and is dynamically adapted to the user’s needs. The proposed control scheme has been successfully tested at hospital Fondazione Santa Lucia (FSL) in Rome with several volunteers presenting different disabilities.
Keywords: Robots autónomos; Minusválidos; Shared control; Autonomous navigation; Wheelchair; Reactive behaviours